Role of Promising Secondary Metabolites to Confer Resistance Against Environmental Stresses in Crop Plants: Current Scenario and Future Perspectives - Chen, Delai; Mubeen, Bismillah; Hasnain, Ammarah; Rizwan, Muhammad; Adrees, Muhammad; Naqvi, Syed Atif Hasan; Iqbal, Shehzad; Kamran, Muhammad; El-Sabrout, Ahmed M.; Elansary, Hosam O.; Mahmoud, Eman A.; Alaklabi, Abdullah; et al. (Frontiers in Plant Science, 2022)
Plants often face incompatible growing environments like drought, salinity, cold, frost, and elevated temperatures. These constraints deferral growth and development, decrease yield and, in worse circumstances can result in plant death. The arsenal of versatile compounds for plant consumption and structure is called metabolites, which allows them to develop strategies to stop enemies, fight pathogens, replace their competitors and go beyond environmental restraints. These elements are formed under particular abiotic stresses like flooding, heat, drought, cold, etc., and biotic stress such as a pathogenic attack, thus conferring a survival strategy on plants. Stress responses of plants are vigorous and include multifaceted crosstalk between different levels of regulation, including regulation of metabolism and expression of genes for morphological and physiological adaptation. To date, many of these compounds and their biosynthetic pathways have been found in the plant kingdom. Metabolites like amino acids, phenolics, hormones, polyamines, compatible solutes, antioxidants, Pathogen related proteins (PR proteins), etc. are crucial for growth, stress tolerance, and plant defense. This review focuses on promising metabolites involved in stress tolerance under severe conditions and events signaling the mediation of stress-induced metabolic changes are presented.